Socio-economic prerequisites for emergence and development of J. Baudrillard’s consumer society theory - A. V. Sidorina (Вестник университета)
This article analyses prerequisites for the emergence of J. Baudrillard’s consumer society theory. First of all, it describes the formation of a sociological approach to consuption analysis as well as studies its differences from economic and psychological approaches. Next, we outline the historical context in which J. Baudrillard’s ideas originated and saw their further development, namely the steady increase in household incomes and improvement in the quality of life in the 1960–1980s, that stimulated an increase in demand for consumer goods and, accordingly, expansion of mass production, considering consumer tastes and preferences. Along with this, the article contains the names of scientists whose views largely determined the main postulates of the sociological approach, including K. Marx’s concept of commodity fetishism and law of increasing requirements, and T. Veblen’s concept of prestigious (ostentatious) consumption. We show that accourding to the abovementioned theoretical and historical prerequisites, the sociological approach considers behaviour of a human as a consumer in a social context for the first time. Thus, the latter turns into a tool for studying the life of an individual, social groups and society as a whole. At the same time, J. Baudrillard poses the process of consumption beyond satisfaction of material needs and designates it as a form of simulation where the iconic value of goods is more important than functional utility.